2013
DOI: 10.1111/j.1525-1594.2012.01570.x
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Protein‐Bound, Hydrophobic Uremic Toxins by a Combined Fractionated Plasma Separation and Adsorption Technique

Abstract: Protein-bound uremic toxins, such as phenylacetic acid, indoxyl sulfate, and p-cresyl sulfate, contribute substantially to the progression of chronic kidney disease (CKD) and cardiovascular disease (CVD). However, based on their protein binding, these hydrophobic uremic toxins are poorly cleared during conventional dialysis and thus accumulate in CKD-5D patients. Therefore, we investigated whether hydrophobic and cationic adsorbers are more effective for removal of protein-bound, hydrophobic uremic toxins than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 35 publications
1
49
0
4
Order By: Relevance
“…With an appropriate displacer, the removal of indoxyl sulfate can be increased up to 3 times compared to baseline removal. Similar efficiency of improved indoxyl sulfate removal was observed only in methods utilizing sorbent technologies [38][39][40] . A 2.4-fold increase of indican (indoxyl sulfate) removal was reported by Meyer et al when adding activated carbon into the dialysate in an in vitro HD model [39] .…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…With an appropriate displacer, the removal of indoxyl sulfate can be increased up to 3 times compared to baseline removal. Similar efficiency of improved indoxyl sulfate removal was observed only in methods utilizing sorbent technologies [38][39][40] . A 2.4-fold increase of indican (indoxyl sulfate) removal was reported by Meyer et al when adding activated carbon into the dialysate in an in vitro HD model [39] .…”
Section: Discussionsupporting
confidence: 64%
“…A 2.4-fold increase of indican (indoxyl sulfate) removal was reported by Meyer et al when adding activated carbon into the dialysate in an in vitro HD model [39] . A fractionated plasma separation and adsorption technique (FPSA) showed a 2.9-fold increase of whole body indoxyl sulfate removal in a 4-hour treatment [40] . For a comparison of indoxyl sulfate removal between our method and other renal replacement therapy modalities, see [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, small charged molecules as, e.g., phenylacetic acid or indoxylsulfate present toxins that adhere to blood proteins such as human serum albumin. [66][67][68][69] Full removal of these toxins by dialysis presents a central and urgent problem of modern nephrology. 68 Precise thermodynamic information on the binding process is the experimental prerequisite for a detailed understanding of the interaction of proteins with polyelectrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Currently, sorbents and nonpharmacological therapies are promising strategies. 33 Indeed, in an in vitro HD model, Meyer et al 34 observed a 2.4-fold increase in the IS removal rate when a sorbent (activated carbon) was added to the dialysate.…”
Section: Discussionmentioning
confidence: 99%